Diagnostic accuracy of isometric knee extension strength as a sarcopenia criteria in older women - Pilar Pérez-Ros; Joaquín Barrachina-Igual; Ana Pablos; Rosa Fonfria-Vivas; Omar Cauli; Francisco M. Martínez-Arnau (BMC Geriatrics)
Abstract Background Muscle strength is one of the most reliable measures used for the identification of sarcopenia. The European Working Group on Sarcopenia in Older People update (EWGSOP2) proposed the use of grip strength and chair stand tests, while clarifying that isometric torque methods can be used when performing the grip strength test is impossible. This study aims to evaluate the diagnostic accuracy of isometric knee extension strength in screening for sarcopenia. Methods This cross-sectional study included community-dwelling women aged 70 years and over. IKE and sarcopenia criteria (EWGSOP2) were assessed. Skeletal muscle mass was assessed by bioelectrical impedance analysis; muscle mass strength by handgrip; and physical performance by the 5 times sit-to-stand test, the Short Physical Performance Battery, and gait speed. The diagnostic accuracy for each sarcopenia criterion was calculated using sensitivity, specificity, positive and negative predictive value, and the area under the curve (AUC). Cutoff points for sarcopenia from IKE were defined with the ROC curve. Results The sample comprised 94 women with a mean age of 75.9 years (standard deviation 5.6, range 70–92), of whom 25.5% (n = 24) met criteria for sarcopenia—mainly severe sarcopenia (73.8%, n = 17). Correlations were observed between IKE and each individually analyzed sarcopenia criterion except skeletal muscle mass, with AUC values exceeding 0.70 in all cases. The IKE cutoff showing the highest accuracy for the diagnosis of sarcopenia was 12.5 kg or less (AUC 0.76, 95% confidence interval [CI] 0.64–0.88; sensitivity: 65.2%, 95% CI 45.7–84.7; specificity 77.4%, 95% CI 60.3–94.5; positive predictive value 62.5%, 95 CI% 42.7–82.3; negative predictive value 88.8%, 95% CI 75.9–100). Conclusions IKE could be a suitable tool for measuring muscular strength in sarcopenia when other strength parameters cannot be assessed or in people with walking difficulties.